Bibliometric Analysis: Mapping the Role of Intellectual Capital in Enhancing Excellence Competing Colleges - Dewi, Gst. Ayu Ketut Rencana Sari; Ramantha, I Wayan; Mimba, Ni Putu SH; Suryana , I Gusti Ngurah Agung (Journal of Applied Business, Taxation and Economics Research, 2024)
In the knowledge economy, competitive advantage in Higher Education (HE) is based on intangible assets of Intellectual capital such as quality in teaching, research, innovation, image, reputation and stakeholder relations. Several studies have been conducted to analyze how intellectual capital contributes to competitive advantage in different contexts. However, it is still rare in the higher education sector. This study aims to fill this gap by providing knowledge mapping and evaluating articles , the role of intellectual capital contribution to competitive advantage in higher education. This study was conducted through a literature study using a bibliometric meta-analysis method approach . This study analyzed 13 publications taken from the Google Scholar database. The results of the study propose the development of variables that are able to improve the relationship between the role of intellectual capital contribution to competitive advantage in higher education comprehensively. The fields of leadership style, innovation and university performance are often associated with the context of university competitive advantage.